Design Method of a Hybrid Power Automobile's Steering Trapezoidal Linkage - Wang Jian; Meng Xiangyang; Ran Ting; Gu Quan (Jixie chuandong)
The steering trapezoid of automobiles can be seen as a link mechanism. It controls the motions of the tyres and influences on the steering Ackermann rate, steering gear ratio, rack force, and so on. A list of steering trapezoid's design parameters based on the benchmark data is given in the study. Front steering trapezoid can be replaced of rear steering trapezoid in the same front suspension system that is proved in this study. The steering trapezoid of a hybrid power automobile is designed taking advantages of Catia V5 parameterized model and front suspension motion model based on Adams. Low cost and low design risk come true through the design method of the steering trapezoid.